PERANAN ORANG TUA DALAM MEMOTIVASI BELAJAR BAHASA INGGRIS PADA ANAK USIA SEKOLAH DASAR - Setyandari, Ana (MAGISTRA, 2014)
his research aims at observing the role of parents in motivating their children in learning English, especially the children who study in Elementary School. The research found that the objective of knowing the background of social status of parents, the number of family, and the parentâs feeling role. However, wealth and the number of family do not always influence the children motivation but the awareness of how important the education is for the children future that will bring good effect to the childrenâs motivation in learning English. Key words : peranan orang tua, motivasi belajar bahasa Inggris.